Enhanced Light Absorption by Horizontally Oriented Diatom Colonies - McFarland, Malcolm; Nayak, Aditya R.; Stockley, Nicole; Twardowski, Michael; Sullivan, James (Frontiers in Marine Science, 2020)
Through in situ holographic imaging of undisturbed water, diatom colonies with high aspect ratios have been found to exhibit preferential horizontal orientation within high biomass subsurface layers. We analyzed holographic video to determine the abundance, size, and orientation of colonies over several vertical profiles from the surface to $\sim$25 m depth. A geometric optics model based on these measurements was then used to estimate light absorption by phytoplankton throughout the water column. Results show a substantial increase in absorption of downwelling irradiance (up to 24.5%) for horizontally oriented colonies when compared to randomized orientations. The effect can be attributed to maximization of the projected area of colonies when oriented perpendicular to the direction of incident light. Formation of high aspect ratio cells and colonies may represent an adaptation to maximize light harvesting in low light environments through interaction with the low velocity shear fields commonly found along pycnoclines at the base of the surface mixed layer. The effect of orientation on light absorption by large chain forming diatoms could influence their abundance and distribution in the ocean as well as the broader structure and function of marine ecosystems.